Direitos, comunidades quilombolas e conservação da biodiversidade: o exemplo do Vale do Ribeira/SP - Souza, Patricia Borba de (2017)
It can be considered that one of the important points to be dealt with in relation to the quilombola communities is the form of their political organization, and, because (or not) of this, how their rules or their Law contribute in a relevant way to their selfempowerment, including giving them a supposed exclusivity in the conservation and use of local biodiversity. Therefore, it was decided to choose as sample to be studied in this thesis 16 communities of the Vale do Ribeira region, in the state of São Paulo: Galvão, Ivaporunduva, Mandira e São Pedro, in a direct way, e Abobral da Margem Esquerda, Bombas, Cangume, Maria Rosa, Morro Seco, Nhunguara, Pedro Cubas e Pedro Cubas de Cima, Pilões, Porto Velho, Praia Grande e Sapatu, through observatory field research. It’s important to emphasize that the Vale do Ribeira region is home to the largest amount of vegetation remaining in the Atlantic Forest of Brazil, and therefore a large part of its territory is protected by different types of Environmental Conservation Units. The process of creating these Conservation Units, however, disregarded the existence and rights of quilombola communities. Part of these Units was created on quilombo lands, imposing restrictions on the traditional way of life of these communities and limiting the possibilities of agricultural and extractive practices. When dealing with the legal order regarding the environments of coexistence of the traditional populations, it was observed, with the researches made for the preparation of this study, that coexist official norms and different forms of juridicity not contemplated by the national legislation, even so, they are endowed with validity, legitimacy, effectiveness and coercivity. In this sense, it was demonstrated in the present research that a social organization based on customary rights almost always maintains an intense relationship with the Law created by the State, being vital for the local environmental sustainability the transit of that community by these two orders, legal/customary and state-owned, since this factor contributes to the maintenance of social harmony, as well as to the conservation of local natural resources. Considering the whole study, what was intended to defend, in this thesis, is that the set of “legal practices” that determine the forms of access and the use of the natural resources, and especially of the land, accepted by all the members who make up the unity of this social group, has the same efficiency as the State laws.